IMPLEMENTASI PERATURAN DAERAH PROVINSI SULAWESI UTARA TENTANG PENGENDALIAN DAN PENGAWASAN MINUMAN BERALKOHOL ( SUATU STUDI DI KOTA MANADO ) - INDRA, MODDY NATASYA; KIMBAL, MARTHEN; LIANDO, FERRY DAUD (JURNAL ADMINISTRASI PUBLIK, 2019)
The Government of North Sulawesi forming Local Regulation Number 4 Year of 2014concerning Control and Supervision of Alcoholic Beverages in North Sulawesi Province, considering thatalcoholic beverages are one of the products of economic value and are closely related to aspects of health,security conditions and public order, morals, mental attitudes and attitudes social society, nowadays thecirculation is increasing and expandingeven reaching all levels of society. Based on data sourced from theMarch 2016 BPS Social and Economic Survey, Manado is the city with the highest consumption of alcoholic87beverages in Indonesia. The purpose of this study is to analyze the implementation of the North SulawesiProvince regulation concerning supervision and control of alcoholic beverages by seeing the Charles O.Jones’s implementation indicator policy. The descriptive qualitative was used in this type of research. Thedescriptive qualitative was used in this type of research. This research is focused on using Charles O.Jones’s theory by seeing the Organization, Interpretation and Application aspects. There are 12 informants.This data gathering technique is gathered through observation, interview, and literature review. Dataanalysis stages : data reduction, data display, verification, and conclusion. The data is given in a form of atable, images, and narration. The descriptive qualitative was used in this type of research. This research isfocused on using Charles O. Jones’s theory by seeing the Organization, Interpretation and Applicationaspects. There are 12 informant. Data collection technique are gathered through observation, interview,and literature review. Data analysis stages : data reduction, data display, verification, and conclusion. Datais presented in the form of tables, figures, and narratives. The result of this research : organization of TheImplementation of the North Sulawesi Province Regulation Concerning Supervision And Control ofAlcoholic Beverages is considered quite good that is seen from the establishment of Cerdas Terpadu TeamSupervision And Control Of Alcoholic Beverages In Manado City. However, the coordinating initiative inthe Cerdas Terpadu team was still seen very rely on Manado city’s industry and trade office. Interpretationhas not yet been manifested well because the vagueness of hangover prevention chapter article 26 about theprevention and repressive ways that are mentioned in this article. Then it is the Second Amendment toMinister of Trade Regulation Number 20 / M-Dag / Per / 4/2014 Regarding Control and Supervision ofProcurement, Distribution and Sales of Alcoholic Beverages which prohibits minimarkets and other retailstores to sell alcoholic beverages type A, hence the principle of Lex Superiori Derogat Legi Inferiori isapplied to Article 7 of North Sulawesi Province Regulation Number 4 Year of 2014. In terms of application,this local regulation of control and supervision in alcoholic beverages that is used in Manado City isconsidered not running very well and optimal because it can still be found easily with alcoholic beveragesthat are sold in retailers and stalls which should not be allowed to sell alcoholic beverages.From this research, we can conclude that the implementation of North Sulawesi ProvinceRegulation Concerning Supervision and Control of Alcoholic Beverages in Manado City has not gone well.It is recommended that North Sulawesi Province Regulation Number 4 Year of 2014 ConcerningSupervision and Control of Alcoholic Beverages needs to be reviewed, the researcher recommends a revisionor amendment to this local regulation. Cerdas Terpadu Team for controlling and supervising the alcoholicbeverages in Manado City is expected to enhance their initiative and to not wait initiative or command fromother agencies. Agencies related to control and supervision of alcoholic beverages are expected to be moreassertive in taking down violators.Keywords : Policy Implementation, Supervision and Control, Alcoholic Beverages